2021
DOI: 10.1590/2177-9465-ean-2020-0380
|View full text |Cite
|
Sign up to set email alerts
|

Dupla jornada de trabalho na enfermagem: dificuldades enfrentadas no mercado de trabalho e cotidiano laboral

Abstract: Resumo Objetivo compreender por meio da lexicografia básica os vocabulários mais frequentes expressos por trabalhadores de enfermagem sobre a experiência de ter uma dupla jornada de trabalho. Método pesquisa qualitativa, realizada com 30 trabalhadores de enfermagem com dupla jornada de trabalho captados pela técnica snowball, entre janeiro e março de 2019, na cidade de Eunápolis, Bahia, Brasil. Os dados foram obtidos por meio de uma entrevista semiestruturada, processados com o auxílio do software Interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
0
6
1
7
Order By: Relevance
“…Working and living in large cities is possibly associated with less time for activities that cause energy expenditure. Instead passive commuting to work, less time for physical exercise and fast food diets become the rule as people living in large cities rush through life, and these habits constitute risk factors for non-communicable chronic diseases [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Working and living in large cities is possibly associated with less time for activities that cause energy expenditure. Instead passive commuting to work, less time for physical exercise and fast food diets become the rule as people living in large cities rush through life, and these habits constitute risk factors for non-communicable chronic diseases [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…However, overweight was only observed among women in the fit model. The double working day, especially for women who have children, further reduces the time available for physical activity and leisure, contributing to greater sedentary behavior [31,33]. Added to this is the fact that overweight gain during pregnancy can be difficult for women to eliminate and to return to their previous weight after pregnancy [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…No âmbito da enfermagem brasileira, historicamente, evidencia-se uma desvalorização salarial e, devido a isso, é comum que seus trabalhadores tenham dois ou mais vínculos de trabalho (alguns, inclusive sem registro oficial), geralmente, na expectativa de um melhor retorno financeiro pelo trabalho desempenhado 19 . Estudo recente, que analisou a relação enfermeiro-população em 58 países, revelou que há uma desigualdade subnacional na distribuição do pessoal de enfermagem.…”
Section: /16unclassified
“…In the context of Brazilian nursing, historically, there has been a devaluation of wages and, due to this, it is common for workers to have two or more employment contracts (some even without official registration), generally in the expectation of a better financial return for the work performed 19 . A recent study, which analyzed the nurse-population relationship in 58 countries, revealed that there…”
Section: /16mentioning
confidence: 99%